STRATEGI BISNIS PENGUSAHA BAKSO DALAM MENGHADAPI KENAIKAN HARGA DAGING SAPI (STUDI KASUS BAKSO PEPO) - Monica Marcella (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
The food and beverage industry is an emerging industry in Indonesia. As a processed beef manufacturer, the annual rise in beef price is a problem for Bakso Pepo. As a result, the company needs to devise a strategy to cope with the challenge. The purpose of this study is to determine the business strategies that can be used by meatball sellers to face the increasing beef price. The business strategies examined in this study are limited to product and pricing strategies. The informants of this study consist of three meatball consumers and three benchmark companies which include peddlers, street vendors, and meatball wholesalers. This research is a qualitative research. Semi-structured interview is used to collect research data, while the Miles and Huberman model is used to analyze the data. Research results suggest that the best product strategies for Bakso Pepo are by maintaining the size of the meatball (form), the composition of raw materials (feature), and the product quality (reliability), as well as creating set menu to minimize the perception of high price. In terms of pricing strategy, the company can implement commodity bundling and second-degree price discrimination strategies during the increase in beef price.